Analysis Of The Perception Of Small Businesses On The Quality Of Routine Municipal Services In The City Of Tshwane, South Africa - Worku, Zeleke (Journal of Applied Business Research, 2017)
A survey was conducted (2012 to 2014) in the City of Tshwane in order to assess and evaluate determinants of adequate municipal services that are routinely provided to operators of start-up business enterprises. Data used in the report come from 1, 058 small businesses. The aim of research was to assess and evaluate the relationship between the quality of services and sustained viability in small business enterprises. The study was conducted against the background of a high failure rate among newly established small businesses in the City of Tshwane. The study found that about 40% of the 1, 058 businesses in the study failed or were not profitable at the end of the 3-year study period. The study showed that there was a significant association between positive perception of business operators on the quality of municipal services provided to them and viability of businesses. The percentage of viable business enterprises that were satisfied with the quality of services provided to them was 87%. The percentage of non-viable business enterprises that were satisfied with the quality of services provided to them was only 13%. Profitability in business enterprises was significantly affected by lack of capacity for fulfilling the business and entrepreneurial needs of newly established businesses [Hazard Ratio = 3.58; P=0.000; 95% C. I. = (1.45, 5.46)], inappropriate policy [Hazard Ratio = 3.19; P=0.000; 95% C. I. = (1.39, 5.28)], and lack of tailor made training programmes directed at newly established small businesses [Hazard Ratio = 2.89; P=0.000; 95% C. I. = (1.24, 4.77)]. In-depth interviews conducted with business operators led to similar findings.
Keywords: City of Tshwane; Small Businesses; Municipal Services; Perception; Hazard Ratio